Role of Metabolic Endotoxemia in Systemic Inflammation and Potential Interventions - Mohammad, Shireen; Thiemermann, Christoph (Frontiers in Immunology, 2021)
Diet-induced metabolic endotoxaemia is an important factor in the development of many chronic diseases in animals and man. The gut epithelium is an efficient barrier that prevents the absorption of liposaccharide (LPS). Structural changes to the intestinal epithelium in response to dietary alterations allow LPS to enter the bloodstream, resulting in an increase in the plasma levels of LPS (termed metabolic endotoxaemia). LPS activates Toll-like receptor-4 (TLR4) leading to the production of numerous pro-inflammatory cytokines and, hence, low-grade systemic inflammation. Thus, metabolic endotoxaemia can lead to several chronic inflammatory conditions. Obesity, diabetes and non-alcoholic fatty liver disease (NAFLD) can also cause an increase in gut permeability and potential pharmacological and dietary interventions could be used to reduce the chronic low-grade inflammation associated with endotoxaemia.